2012
DOI: 10.1002/arch.21012
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Moringa oleifera FLOWER EXTRACT ON LARVAL TRYPSIN AND ACETHYLCHOLINESTERASE ACTIVITIES IN Aedes aegypti

Abstract: Aedes aegypti control is crucial to reducing dengue fever. Aedes aegypti larvae have developed resistance to organophosporous insecticides and the use of natural larvicides may help manage larval resistance by increasing elements in insecticide rotation programs. Here, we report on larvicidal activity of Moringa oleifera flower extract against A. aegypti L(1), L(2), L(3), and L(4) as well as the effect of flower extract on gut trypsin and whole-larval acetylcholinesterase from L(4.) In addition, the heated flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…Extracts and compounds with larvicidal activity against A. aegypti have been reported to disrupt the activity of larval digestive enzymes and it is well known that larvae of A. aegypti produce trypsin-like enzymes which are essential for digestive process and thus nutrition and development (Agra-Neto et al, 2014;Kunz, 1978;Napoleão et al, 2012;Pontual et al, 2012Pontual et al, , 2014. The lactone 5a was able to inhibit L4 gut trypsin (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Extracts and compounds with larvicidal activity against A. aegypti have been reported to disrupt the activity of larval digestive enzymes and it is well known that larvae of A. aegypti produce trypsin-like enzymes which are essential for digestive process and thus nutrition and development (Agra-Neto et al, 2014;Kunz, 1978;Napoleão et al, 2012;Pontual et al, 2012Pontual et al, , 2014. The lactone 5a was able to inhibit L4 gut trypsin (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The assay was performed according to Pontual et al (2012). Groups of 50 live L4 were immobilized by incubation (10 min) at 4°C and their guts were removed with the aid of a needle and stereomicroscope.…”
Section: Effect Of Lactones On Trypsin Activity From L4 Gut Extractmentioning
confidence: 99%
“…One of the strategies to eliminate this mosquito is the use of synthetic insecticides belonging to the classes organochlorines, organophosphates and pyrethroids, which generally act on the nervous systems of insects . Although effective, the inadequate management of these insecticides led to the emergence of resistant insect populations, and as a consequence of increased resistance of pests to chemical insecticides, research on natural and biodegradable insecticides that promote larval mortality and avoid the emergence of resistant strains has increased …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the extract of Moringa oleifera flowers with trypsin inhibitor activity show larvicidal activity on Aedes ageypti [46,47]. Agra-Neto et al confirmed that lectins WSMoL and cMoL from Moringa oleifera seeds show larvicidal activity on fourth-stage Aedes ageypti larvae by affecting the digestive and detoxifying related enzymes of larvae [18,48].…”
Section: Schistosomiasis Is a Chronic Tropical Disease Caused By Paramentioning
confidence: 98%